Peran Guru dalam Meningkatkan Kedisiplinan Siswa pada Pembelajaran PPKn di SMP Negeri 2 Tompaso Kabupaten Minahasa - Syalom Trivena Injili Pangaila; Julien Biringan; Telly Delly Wua (CV. Kurnia Grup, 2026)
This study aims to analyze the role of teachers in improving student discipline in Pancasila and Citizenship Education (PPKn) learning at SMP Negeri 2 Tompaso, Minahasa Regency. The approach used was qualitative with descriptive data presentation, because this study focuses on observations of real phenomena occurring in the field. This method allows researchers to describe conditions and problems in detail and understand the interactions between teachers and students in the learning process. The results show that PPKn teachers play a crucial role in guiding, advising, providing motivation, and being role models for students in instilling discipline. The personal approach applied by teachers to students facing difficulties helps strengthen discipline effectively. In addition, the application of Pancasila values in learning also supports the formation of students' disciplined character. Other factors, such as student awareness, school environmental support, and parental involvement, also contribute to improving discipline. This study confirms that the role of teachers is very strategic in shaping students' disciplined attitudes, thus creating a more orderly, effective, and conducive learning process.